Self-Efficacy of Micro Businesses in Facing the COVID-19 Pandemic in Blitar District - Tri Indah Yuwono (Universitas Airlangga, 2021)
This study aims to determine the dynamics and self-efficacy factors of micro businesses in dealing with theCOVID-19 pandemic in Blitar District. The method used is qualitative with a case study approach. The subjectsin this study were micro entrepreneurs in Blitar District. Data collection method is done by using the interviewmethod. The data analysis technique used in this research is content analysis. Based on research results. SubjectI is optimistic and has the confidence to overcome the problems of his business amid the COVID-19 pandemic.In addition, subject I has a lot of innovations or ideas that are applied so that the business can continue tosurvive in the midst of a pandemic. Factors influencing the self-efficacy of subject I are environmental support,past experience, physiological and psychological factors, motivation, and gratitude to God. In subject II did nothave a sense of confidence and tended to be pessimistic in dealing with the COVID-19 pandemic, Subject II feltthat he had no idea and a way out to continue his business in the midst of a COVID-19 pandemic, the factorsaffecting subject II's self-efficacy were almost the same as subject I namely environmental support, pastexperience, physiological and psychological factors, motivation, and gratitude to God. The findings of this studyare that there are some similarities in positive factors that affect self-efficacy between the two subjects butprovide different outputs of self-efficacy.